The Construction of Husein Ja'far's Character in the Digital Preaching Space: A Critical Discourse Analysis of the Contents of "Pemuda Tersesat” - Muhammad Ruhul Qudus; Siti Kholifah; Mangku Purnomo (Communicatus: Jurnal Ilmu komunikasi, 2025)
The shift of da'wah to the digital space demands a reinterpretation of religious authority, no longer solely dependent on formal scholarly legitimacy but also on the formation of a persona through communication practices. However, previous research on Pemuda Tersesat has focused on humor and da'wah messages, without examining how the preacher's persona is discursively constructed and serves as a basis for religious legitimacy. This study aims to explain how the persona of Husein Ja'far is constructed in Pemuda Tersesat and how this construction produces religious authority and moderation in the digital space. Using a qualitative approach with Norman Fairclough's Critical Discourse Analysis model, this study analyzes 10 selected episodes through the dimensions of text, discursive practices, and social practices. The results show the formation of a humorous, dialogical, rational, and moderate preacher persona, reinforced by audience responses in the form of recognition, emotional closeness, and moral legitimacy. This persona not only shapes a digital religious image but also encourages real social participation through collective philanthropic movements. The study concludes that the digital da'wah persona is a discursive construction that generates symbolic power and is a performative instrument of religious moderation. Theoretically, this study enriches the study of digital communication and da'wah by emphasizing the critical relationship between language, authority, and social practices in the formation of contemporary religious authority.